The Alzheimer’s Questionnaire: A Proof of Concept Study for a New Informant-Based Dementia Assessment - Sabbagh, Marwan N. (2010)
The aim of this pilot study is to determine the feasibility and clinical utility of a brief, informant-based screening questionnaire for Alzheimer’s disease (AD) that can be administered in a primary care setting. The Alzheimer’s Questionnaire (AQ) was administered to the informants of 188 patients in 3 dementia clinics (50 cognitively normal, 69 mild cognitive impairment (MCI), 69 AD). Total score for the AQ is based upon the sum of clinical symptom items in which the informant responds as being present. Clinical symptoms which are known to be highly predictive of the clinical AD diagnosis are given greater weight in the total AQ score. The mean time of administration of the AQ was 2.6 ± 0.6 minutes. Sensitivity and specificity were found to be high for detecting both AD (98.55, 96.00) and MCI (86.96, 94.00) with ROC curves yielding AUC values of 0.99 and 0.95, respectively. This pilot study indicates that the AQ is a brief, sensitive measure for detecting both MCI and AD and could be easily implemented in a primary care setting.